E-BPHTB: STRATEGI MENINGKATKAN PENERIMAAN BPHTB SELAMA PANDEMI COVID-19 - Tsamarah Widad Wadhiah; Moh. Faisol (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
The aims of this reseach to find out the strategy implemented by BPPKAD Sumenep Regency in increasing local tax revenue (BPHTB) during the Covid-19 pandemic. researchers used qualitative methods with a case study approach to determine the strategy undertaken. Researchers conducted in-depth interviews with three BPPKD employees and one notary. Interview data were analyzed using qualitative data analysis (data reduction, data presentation, conclusion, and verification). The results of this study provide information that the steps taken by BPPKAD in maximizing tax revenues are by developing the E-BPHTB system, so that the tax collection process is easier and faster. However, the notary as one of the users is still unfamiliar, so it takes time to adapt to using the system. The implication of this research is that the use of information technology (E-BPHTB) can increase service effectiveness and tax revenue, but requires maximum socialization so that it is easy to adapt.